Trade, poverty and food security: A survey of recent research and its implications for East Africa - Huw Lloyd-Ellis; Ardyn Nordstrom (Queen's University, Department of Economics, 2021)
We survey the latest research on the linkages between international trade, regional integration, poverty and food security in developing economies and draw out its implications for East Africa and future research. While there is now an extensive literature on the impacts of trade reform on poverty outcomes, research on the actual and potential effects of trade and regional integration on food security is much more limited. This reflects inconsistencies in the definition and measurement of food security, substantial data limitations, and the complexity of food systems themselves. Nevertheless, we argue that there is an urgent need and considerable scope for further research on these linkages.
Keywords: F13; Q17; Q18; I3; D63; 330; Trade; food security; poverty; East Africa; regional integration; inequality; survey